Swimming energy training in the 21st century: The justification for radical changes - Rushall, B. S. (Swimming Science Bulletin, 2011)
For a variety of reasons, the accurate understanding of the energy requirements of swimming races has been absent from swimming coaching circles. The programming reasons and implementations of conditioning stimuli at training have largely been irrelevant for stimulating improvements in race performances. The traditional physiology of swimming energy use should be discarded. Swimming is a fully supported, partially-intense activity. That sets its energy demands apart from non-supported, total-body activities such as running and cross-country skiing. Research implications gained from those activities should not be used as guidelines for physiological responses in competitive swimming. Recent swimming research has indicated that in single races, the alactacid and aerobic energysystems are dominant while a considerable amount of Type IIb fibers are developed through specific training and add to the oxidative energy pool for racing. The physiology of traditional swimming practices is discretely different to that of racing. Thus, traditional practices are largely irrelevant for racing and do not provide an avenue for race improvements. By revising what is known about human physiology and neuromuscular patterning, the case was made for race-specific techniques and their energizing as being inextricably yoked and represented as discrete brain activation patterns. The result is that the only way to improve swimming velocities for specific races is to practice swimming at those velocities or slightly faster. The term "ultra-short training at race-pace" is appropriate. Traditional practice programs and items do not accommodate much high-intensity work. Yet, the physiological and mechanical benefits of high-intensity (race-pace) training are more than any other form can provide, particularly those commonly seen in swimming practices. Research has shown how to complete large amounts of race-pace training without incurring exhausting aerobic fatigue. It is proposed that ultra-short training at race-pace is the format upon which all race-pace training should be patterned. The benefits of race-pace training in swimming exceed those of other forms of interval, repetition, and continuous training. The physiology, neuromuscular patterning, and implementation strategies for race-pace training are explained in some depth. Several factors that maximize the training effects of race-pace sets and that are contrary to common coaching practices are also explained. This far-reaching paper attempts to make the case for drastic changes in the programs and behaviors of swimming coaches. Increasing relevant and decreasing irrelevant training is proposed. It is evidence-based with extensive references to support most of the premises in its arguments. Consequently, it is hard to argue against as it is more defensible than current belief-based coaching behaviors and practices. Radical changes in swimming coaching are in order!